Comparaison Quantitative Et Qualitative Des Huiles Essentielles De Rosmarinus Officinalis Obtenues Par Différentes Méthodes - Taha EL Kamli; Faouzi Errachidi; Noureddine Eloutassi; Houmane Majid; Rachida Chabir; Abdellatif Bour (European Scientific Journal, ESJ, 2017)
Rosmarinus officinalis is among the most abundant medicinal and aromatic plants in Morocco. There are several factors that influence the yield of quality and quantity of essential oils of this plant. This work focuses on the study, characterization and comparison of the chemical composition of essential oils of Rosmarinus officinalis. The raw material studied is originally from the central part of northern Morocco (Skoura M'Daz region, Eastern Middle Atlas). The essential oils of rosemary were obtained by three different extraction methods : DA: Artisanal distillation, the essential oils were obtained directly from small cooperatives using a very traditional (nonindustrial) method and based on the technique of Steam distillation ; DI: Industrial distillation which is also based on Steam distillation; DC: hydrodistillation by clevenger apparatus Laboratory. The physicochemical characterization of essential oils focuses on the search for the yield of % essential oil with regard to the dry rosemary biomass, density, refractive index and rotatory power. The chemical analyzes were carried out by gas chromatography (GC), they identified 11 components representing more than 99.64% of the essential oil and indicate that the chemotype is 1.8 cineole and is varied according to the method (DI: 48.83%, DA: 41.28% and DC: 51.77%). In conclusion we have shown a quantitative and qualitative loss of essential oils due to the extraction method of essential oils, which has direct repercussions on the economy of rural Morocco and consequently on their sustainable development.